Pedagogical basis of the development of future teachers’ didactic culture: Key components of formation - Kantayeva, Gulnur; Baltynova, Aizhan; Dossanova, Altynay; Ainash, Alzhanova; Ospanova, Farida (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study is to explore how the development of professional and didactic culture is shaped by the pedagogical ideal of an integral teacher’s personality. It aims to understand how didactic culture influences the teacher's professional competence, self-regulation, and self-development, ultimately contributing to their overall professional and pedagogical effectiveness. This research adopts a qualitative and interpretive approach, focusing on the theoretical and conceptual analysis of the professional and didactic culture of future teachers. It integrates pedagogical, psychological, and sociological perspectives to examine the interplay between the teacher's personal qualities, professional knowledge, didactic skills, and their internal culture. The study employs a literature review and theoretical modeling to explore the dynamics of professional self-regulation and the role of internal culture in shaping teacher competence. It is highlighted that didactic culture plays a dual role in shaping the teacher's professional identity and competence. It not only provides a framework for the teacher's external professional image but also fosters an internal culture that drives self-development and self-regulation. This internal culture is a critical component of professional and pedagogical culture, enabling teachers to achieve and sustain high levels of competence.